Project management : a systems approach to planning, scheduling, and controlling - Kerzner, Harold (Wiley, 2022)
"This Thirteenth Edition of the bestselling "bible" of project management maintains the streamlined approach of prior editions and continues to align with PMI's Project Management Body of Knowledge (PMBOK). New content has been added to this edition on project health checks; growth of strategic project management; business models; Lean project management; artificial intelligence; growth of new metrics and KPIs and much more"-- Provided by publisher.
Includes index.
Keywords: Project management.; Project management -- Case studies.; elektronické knihy; electronic books